Evaluating the German (New Keynesian) Phillips Curve - Rolf Scheufele (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2008)
This paper evaluates the New Keynesian Phillips Curve (NKPC) and its hybrid variant within a limited information framework for Germany. The main interest rests on the average frequency of price re-optimization of firms. We use the labor income share as the driving variable and consider a source of real rigidity by allowing for a fixed firm-specific capital stock. A GMM estimation strategy is employed as well as an identification robust method that is based upon the Anderson-Rubin statistic. We find out that the German Phillips Curve is purely forward looking. Moreover, our point estimates are consistent with the view that firms re-optimize prices every two to three quarters. While these estimates seem plausible from an economic point of view, the uncertainties around these estimates are very large and also consistent with perfect nominal price rigidity where firms never re-optimize prices. This analysis also offers some explanations why previous results for the German NKPC based on GMM differ considerably. First, standard GMM results are very sensitive to the way how orthogonality conditions are formulated. Additionally, model misspecifications may be left undetected by conventional J tests. Taken together, this analysis points out the need for identification robust methods to get reliable estimates for the NKPC.
urn:nbn:de:gbv:3:2-7359
Keywords: E31; C13; C52; 330; Inflation dynamics; Phillips Curve; Weak Instruments; Optimal Instruments; New-Keynesian Phillips Curve; Schätzung; Deutschland